2021
DOI: 10.9734/jammr/2021/v33i2431240
|View full text |Cite
|
Sign up to set email alerts
|

Gastroduodenal Strongyloidiasis Causing Protein Losing Enteropathy – A Case Report and Brief Review of Literature

Abstract: Strongyloidiasis is a common disease worldwide, has a complex life cycle and infect humans percutaneously. We report case of 46-year-old woman, presented with complaints of abdominal pain, and distension. She was on PPI (Proton Pump Inhibitors) for recurrent gastritis. She also  gives history of steroid intake for joint pain. USG abdomen showed moderate ascites. Upper GI endoscopy showed diffuse erythematous gastric mucosa with subtle mosaic pattern and edematous duodenal mucosa showing patchy erythema. Histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this search, we found that endoscopy often revealed chronic gastritis or severe erosive duodenitis, with or without eosinophilic infiltration [ 4 , 16 ]. We can also see larvae of the strongyloides in these areas [ 4 , 17 ].However, in another case from before 2000, they performed X-ray, which showed duodenal dilatation and a delay in the third part of the loop with abnormal motility [ 18 ]. Our patient underwent full abdominal enhancement CT, which suggested that the small intestine had gas effusion and dilation.…”
Section: Discussionmentioning
confidence: 99%
“…In this search, we found that endoscopy often revealed chronic gastritis or severe erosive duodenitis, with or without eosinophilic infiltration [ 4 , 16 ]. We can also see larvae of the strongyloides in these areas [ 4 , 17 ].However, in another case from before 2000, they performed X-ray, which showed duodenal dilatation and a delay in the third part of the loop with abnormal motility [ 18 ]. Our patient underwent full abdominal enhancement CT, which suggested that the small intestine had gas effusion and dilation.…”
Section: Discussionmentioning
confidence: 99%